Business ethics, 2nd edition - Khalid Ali, Khalidah; Ramly, Zulkufly; Lau, Teck Chai (Oxford University Press, 2018)
This comprehensive second edition caters for undergraduate students pursuing business and accountancy courses at local institutions of higher learning. It is a timely book which offers in-depth discussions on business ethics fundamentals from a local perspective. Spanning 12 chapters, the book starts off with the key concepts and theories of business ethics, followed by important topics such as ethical leadership and corporate culture, corporate governance, corporate social responsibility (CSR), business ethics and information technology (IT), ethics and the environment, as well as ethics in the global environment. What sets this book apart in the market is the inclusion of uncommonly discussed topics, namely consumer ethics and ethics from Islamic perspectives. Students will be able to relate what they have learned to the real world with ease through the various, authentic ‘Cases for Review’ that punctuate the topics covered in the chapters. Each chapter also ends with a glossary of the key concepts and terms covered, along with exercises for further discussions and practice. Besides, this edition includes additional end-of-chapter case studies to create awareness on ethics and its significance in business within a glocal context.